2021
DOI: 10.12688/f1000research.52889.2
|View full text |Cite
|
Sign up to set email alerts
|

Boesenbergia pandurata application in Goldfish (Cyprinus carpio) Feed to Enhancing Fish Growth, Immunity System, and Resistance to Bacterial Infection

Abstract: Background: This study investigated how the inclusion of Boesenbergia pandurata extract (BPE) in goldfish feed affects fish growth, immunity, and resistance to infection by Aeromonas hydrophila and Pseudomonas fluorescens.   Methods: Four fish feeds, were prepared by adding BPE at the concentrations of 0 (control), 2, 4, and 6 g kg-1, respectively, and 120 goldfish (Cyprinus carpio; initial weight 5 g) were separated into 12 boxes and fed with specific pellets and examined thrice. The experiment lasted 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The use of crude extract has multiple effects on fish and shrimp, hampering bacterial pathogens [15,16], worm parasites [19], and viruses [20] and improving the immune systems of fish and shrimp [21][22][23]. Some research has even shown that plant extract can be prebiotics and synbiotics [26] which are excellent for improving growth [14,22,26,27,28] and the quality of water [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The use of crude extract has multiple effects on fish and shrimp, hampering bacterial pathogens [15,16], worm parasites [19], and viruses [20] and improving the immune systems of fish and shrimp [21][22][23]. Some research has even shown that plant extract can be prebiotics and synbiotics [26] which are excellent for improving growth [14,22,26,27,28] and the quality of water [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…One of the save methods to increase production in shrimp pond is through the use of sour eggplant (Solanum ferox), finger root (Boesenbergia pandurate), and lempuyang (Zingiber zerumbet) extracts. These three plants have phytochemicals, namely flavonoid and alkaloid with antibacterial and immunostimulant functions [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential antiparasitic plants is sour eggplant, which contains solasodine, a steroidal glycoalkaloid compound. Some studies have shown that solasodine has antifungal [19,20], antibacterial [21][22][23][24]47,48], anticancer [25,26,45,46], and antiparasitic potencies as well as several other important activities [27].…”
Section: Introductionmentioning
confidence: 99%
“…that infects goldfish (C. carpio). These three extracts have been widely found to have antibacterial effects against Aeromonas hydrophila, Pseudomonas fluorescens, Vibrio harveyi, and V. haemolytic [28][29][30][31][32][33][34][35][36]47,48]. Various contents (e.g., alkaloids, flavonoids, solasodine, zerumbet, and panduratin) are secondary metabolic materials in these three extracts capable of negatively affecting pathogens (e.g., bacteria, fungi, protozoa, crustacea, nematodes).…”
Section: Introductionmentioning
confidence: 99%